2015
DOI: 10.1016/j.ctim.2015.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Herbal medicine Davaie Loban in mild to moderate Alzheimer’s disease: A 12-week randomized double-blind placebo-controlled clinical trial

Abstract: Our findings suggest that DL may be effective in improvement of memory in patients with mild-to-moderate Alzheimer's disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…The strongest-docking triterpenoid ligands to TcAChE were 4,23-dihydroburic acid ( E dock = −135.8 kJ/mol) and 3-acetoxy-5,12-ursadien-24-oic acid ( E dock = −131.7 kJ/mol); olibanumol N docked strongly with MmAChE ( E dock = −133.0 kJ/mol). The excellent docking properties of Boswellia triterpenoid ligands to acetylcholinesterase supports the clinical use of frankincense to treat Alzeimer’s disease [ 41 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The strongest-docking triterpenoid ligands to TcAChE were 4,23-dihydroburic acid ( E dock = −135.8 kJ/mol) and 3-acetoxy-5,12-ursadien-24-oic acid ( E dock = −131.7 kJ/mol); olibanumol N docked strongly with MmAChE ( E dock = −133.0 kJ/mol). The excellent docking properties of Boswellia triterpenoid ligands to acetylcholinesterase supports the clinical use of frankincense to treat Alzeimer’s disease [ 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…resins have been used in Persian traditional medicine as an anti-Alzheimer’s agent [ 36 , 37 ]. Animal models (rat) of Alzheimer’s disease [ 38 , 39 , 40 ] and human clinical trials [ 41 , 42 ] showed beneficial effects on memory with frankincense.…”
Section: Resultsmentioning
confidence: 99%
“…Through in vivo and in vitro studies, various components of herbal medicine have been found to possess the ability to intervene in aging-related diseases by activating telomerase, increasing antioxidant capacity, reducing apoptosis and anti-inflammatory activities, and regulating aging-related pathways and exosomes. We also summarized the clinical randomized controlled trials (RCTs) of herbal medicine in the treatment of aging-related diseases ( Table 3) [240][241][242][243][244][245][246][247][248][249][250]. These trials found that herbal medicine displays certain clinical efficacy in the treatment of agerelated diseases such as type 2 diabetes, vascular dementia, AD, and atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…calamus has also been clinically investigated as a monotherapy as well as in combination with other medicinal herbs in healthy subjects and sufferers of various metabolic and neurological ailments. Most clinical research has looked at the A. calamus effect on obesity, depression, neuroprotection, and cardiovascular disease [178][179][180][181][182][183][184][185][186][187][188][189][190][191]. The data obtained so far can be found in Table 5.…”
Section: Clinical Reportsmentioning
confidence: 99%